Rules of ergonomics and digitization of working life: An exploratory study in the Babylon Health Department - Hussein Ali Muhammad AL-Mahdawi; Fouad Yousif Abdul Rahman Mahmoud Al-Jubouri (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This study seeks to shed light on one of the relatively modern branches of science, "the rules of Ergonomics", which is concerned with the healthy and safe interaction between the human element and other elements, and to analyze the work environment through the proper design of these elements, and the evaluation and analysis of various work activities and functions. The research was based on the idea that the rules of Ergonomics have a significant and effective role in the digitization of work life. The researcher adopted the exploratory study using the questionnaire, the Likert quinquennial scale, and descriptive and statistical methods in quantitative treatment. In the organization under study, which indicates the validity of the hypotheses of the study and in varying proportions, in addition to the researcher providing some necessary recommendations in this regard.